Galilei-invariant higher-order equations of burgers and korteweg-de vries types - Boiko, V. M.; Fushchich, V. I. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We describe nonlinear Galilei-invariant higher-order equations of Burgers and Korteweg-de Vries types. We study symmetry properties of these equations and construct new nonlinear extensions for the Galilei algebra $AG(1, 1)$.